"A Home for Me When I Am So Far from Home": Perceptions of Libraries by Immigrant Mothers in Language Acquisition and Cultural Acclimation. Issue 3 (3rd July 2017) - Branyon, Angela P.
ABSTRACT: This phenomenological study examines the unique perceptions of immigrant women concerning the public library as a meeting place, a support to integration into American culture, and a provider of programs for acquisition of the English language. The library offers a place for observing the culture of the new country from a distance to active participation; it is an arena for comfort and consolation in a difficult life situation as well as an arena for activity and participation. It provides support in developing friendships, acclimating to a new culture, learning a new language, and providing avenues to employment. Three mothers, who fulfilled the criteria for the study, were selected from an initial focus group. Women from Kurdistan, Mexico, and Indonesia were interviewed individually to gain an understanding on the issues brought forth in the focus group. They participated in interviews over the course of 6 months. These programs became a fortuitous blending of an established community with a group of families looking for a support community in a new country. This study has implications for institutions serving immigrants as they look to find a community of support, to learn English, and to acclimate to American culture as they create a comfortable identity that blends their home country with the new country.